Post-Operative Outcomes of Coronary Artery Bypass Surgery in Young Adults - Muhammad Tariq, Waqar Masud Malik, Kifayat Ullah, Kiran Jamal, Attiya Hameed Khan, Abdul Nasir, Syed Shahkar Ali Shah (Pakistan Journal of Medical & Health Sciences, 2024)
Background: CABG is extensively studied surgical procedure but the data shows little about younger population. The gold standard for treating TVCAD is coronary bypass surgery with better long-term outcomes and lesser reintervention. Young adults who have coronary arteries revascularized are a specific category of sufferers, with research on cardiovascular proceedings. Aim: To identify the risk factors and to determine the postoperative outcomes in young patients encountering CABG. Methodology: This retrospective empirical groundwork was carried out at Peshawar institute of cardiology, included (n=95) adults, who were diagnosed with coronary artery disease and underwent CABG surgery. Data was extracted from electronic medical record (EMR) and by using SPSS version 26.0, the data was analyzed. Results: Mean age of the patients (43.24±3.940), mean BMI (27.8249±4.32135), mean pulse rate (80.79±13.808), mean systolic BP (134.40±19.168), mean diastolic BP (83.86±13.901). Major risk factors observed were both DM and HTN 33.7%, use of tobacco and HTN20%. Correlation of age showed significant linear relationship with ventilation time, ICU stay, CCS class with NYHA at P<0.01. Similarly, previously diagnosed STEMI patients showed significant linear relationship with mortality at P<0.05. Conclusion: According to the consequences of the study it is presumed that in young patient’s lower rates of morbidity and in hospital mortality was observed as compared to older counterparts. Furthermore, detailed multicenter study in this area is needed with higher sample size and long-term effects for extended periods of time to confirm better results. Keywords: Coronary artery disease,Percutaneous coronary intervention, Cardiopulmonary bypass